Buletin Peternakan : Strategi Peningkatan Adopsi Inovasi pada Peternakan Sapi Perah Rakyat di Daerah Istimewa Yogyakarta, Jawa Tengah, dan Jawa Timur - Septi Nur Wulan Mulatmi,, Budi Guntoro, Budi Prasetyo Widyobroto, Sudi Nurtini, Ambar Pertiwiningrum (Peternakan UGM, 2016)
This study was aimed to formulate strategies for increasing adoption innovation in the smallholder dairy farms. The study was conducted in May to July 2015.